Copy number variation in development disorders, malformative syndrome and short stature in Peru - Abarca Barriga, Hugo H. (2020)
Objective: to establish the ratios of the copy number variations and regions of homozygosity through chromosomal microarray analysis (CMA) in children with neurodevelopmental disorders: development delay (DD), intellectual disability (ID), and/or autistic spectrum disorder (ASD), malformative syndrome (MS) and idiopathic short stature (ISS). Materials and methods: we evaluated 367 Peruvian children diagnosed clinically with ID, DD, ASD, ISS and MS to whom performed chromosomal microarray analysis in peripheral blood (750K CGH + SNP), between the years 2016-2018. Results: patients' age fluctuated between 4.8 months and 18 years old, with an average of 5.6 years old. The most frequent diagnoses were development delay (48%) and intellectual disability (30%). Abnormal results (pathogenic variants, likely pathogenic variants, uniparental disomies and loss of heterozygosity> 2.5%) were reported in 50.3%. The 53.28% of the cases with a diagnosis of intellectual disability and 47.92% of development delay showed abnormal results; while the children with short stature syndromic, malformative syndrome, and autistic disorders spectrum disorders showed abnormal results in 52.38%, 52% and 20% respectively. Additionally, we found that 6.25% of parents were non-declared consanguinity. Conclusions: Abnormal results found in our study was a higher ratio than other international reports regardless of the clinical diagnosis. Furthermore, we show a most rate of non-declared consanguinity in relation with previous reports.